2016
DOI: 10.1111/jeb.12889
|View full text |Cite
|
Sign up to set email alerts
|

Drift effects on the multivariate floral phenotype ofCalceolaria polyrhizaduring a post‐glacial expansion in Patagonia

Abstract: Quaternary environmental changes substantially impacted the landscape and promoted rapid evolutionary changes in many species; however, analyses of adaptive phenotypic variation in plants have usually neglected the underlying historical context. Here, we associate phylogeography and phenotypic evolution by analysing the divergence of Calceolaria polyrhiza multivariate floral phenotype after a Pleistocene post-glacial expansion in Patagonia. Phenotypic matrix (P) properties (size, shape, orientation and phenoty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 54 publications
1
10
0
Order By: Relevance
“…We used the R script from Maubecin et al . () to evaluate the correlation between responses to selection.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We used the R script from Maubecin et al . () to evaluate the correlation between responses to selection.…”
Section: Methodsmentioning
confidence: 99%
“…The average correlations range from zero, if matrices are completely different, to one, if both matrices are similar. The magnitude of the response vectors was calculated as the vectors' length ratio (Maubecin et al, 2016). This ratio assesses the similarity in matrix size; if two matrices are equal, the magnitude of the response is expected to be the same for both matrices, and the ratio will be equal to one.…”
Section: Variation In the Magnitude And Patterns Of Phenotypic Integrmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results provide some insights about the evolution of variances and covariances among floral traits. First, proportional changes in matrix size accounted for a significant amount of variation among P ‐matrices (changes in the total amount of phenotypic variance) suggesting a role of drift (Jones et al., ; Maubecín et al., ; Roff, ). Second, simulations also suggested that variation among species in the magnitude of corolla integration occurred independently from the transition from bee to hummingbird pollination.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we performed a series of numerical simulations to examine the potential role of drift and selection on the observed variation of the major axes of the variance-covariance space. Drift is expected to influence the total amount of variance of a matrix (Jones, Arnold, & Bürger, 2003;Roff, 2000), whereas stabilizing and correlational selection may influence phenotypic integration (Maubecín, Cosacov, Sérsic, Fornoni, & Benitez-Vieyra, 2016).…”
Section: Introductionmentioning
confidence: 99%